Neuroinflammation and nutrition in Alzheimer’s disease - Hyoungshin Park; Mya Ni; Yvonne Le (Frontiers in Neurology)
The brain contains approximately 100 billion neurons and over 200 billion glial cells, which are integral to the neuronal networks that support normal brain function in the central nervous system. The complexity of the brain makes the diagnosis and treatment of neurodegenerative disease particularly challenging. Neuroinflammation and neuronal cell death contribute to the development of neurodegenerative diseases such as dementia. Dementia refers to a decline in memory and thinking ability, affecting approximately 55 million people worldwide. Owing to the association of multiple factors, including amyloid-β plaque, tau-fibrillary tangles, neuroinflammation, nutritional defects, and genetic mutations, the exact cause of the most common type of dementia, Alzheimer’s disease, remains elusive. These multiple factors may cause damage to neurons and glial cells, leading to neurodegeneration. Very few therapeutics are available for neurodegenerative diseases due to the limited understanding of their pathogenesis, resulting in the lack of biomarkers and drug targets. Recent attention has shifted toward addressing modifiable risk factors such as unhealthy diets and lifestyles to delay the onset of Alzheimer’s disease. Unhealthy diets that consist of saturated fatty acids and refined sugars, with other multiple risk factors, increase neuroinflammation and oxidative stress, furthering cognitive decline and progression of neurodegeneration. Mitigating these risk factors with antioxidants, anti-inflammatory-based nutrition, and multidomain lifestyle intervention, which may include physical exercise, cognitive stimulation, and social engagement, may delay the development of neurodegenerative diseases and cognitive decline. In this review, we focus on the role of neuroinflammation in contributing to neurodegeneration and dietary influence in Alzheimer’s disease.